Organizational Change Management, Institutional Leadership, and Faculty Capacity Development Supporting Sustainable Technology Integration in Maritime Vocational Education - Titis Ari Wibowo; Tri Cahyadi; April Gunawan Malau; Larsen Barasa (International Journal of Educational Practice and Policy, 2026)
The accelerating pace of technological transformation in the global maritime industry demands corresponding institutional readiness within maritime vocational education systems. Yet, the organizational structures, leadership capacities, and faculty competencies required to sustain such transformation remain insufficiently understood. This study investigates how organizational change management, institutional leadership practices, and faculty capacity development collectively support sustainable technology integration in maritime vocational education in Indonesia. Employing a qualitative research design, data were collected through semi-structured interviews with 12 maritime education experts, 18 vocational lecturers, and 15 recent graduates from three maritime polytechnic institutions. Data analysis followed a three-stage procedure encompassing thematic analysis, cross-group comparison, and narrative synthesis. The findings reveal five interconnected themes: strategic leadership alignment, organizational culture readiness, structured faculty professional development, industry–institution collaborative governance, and sustainability-oriented curriculum embedding. Cross-group comparisons indicated that while experts emphasized systemic reform, lecturers prioritized pedagogical support, and graduates highlighted experiential coherence. The study contributes a contextually grounded framework demonstrating that sustainable technology integration requires simultaneous and coordinated advancement across leadership, organizational culture, and human capacity dimensions rather than isolated interventions.